Comparing Fishing Technology of Korea and Indonesia: An Evaluation of the Efficiency, Quality, and Sustainability of Fishery Resources (Maritime Park: Journal of Maritime Technology and Society, 2023)
This article compares the fishing technologies used by Korea and Indonesia in efficiency, quality, and sustainability. The author uses the literature study method by collecting secondary data from various sources, such as scientific journals, government reports, mass media, and official websites. The analysis shows that Korea has more sophisticated, modern, and integrated fishing technology than Indonesia. This technology allows Korea to catch fish more efficiently and produce high-quality fishery products. In addition, Korea also has a fishery resource management system that is better than Indonesia. Korea implements various policies and regulations to maintain the sustainability and productivity of fishery resources. Indonesia still needs to face various problems and challenges in the fisheries sector, such as overfishing, fish theft by foreign vessels, damage to the marine environment, and low-quality fishery products. Indonesia also needs more research and development of fishery technology. This article recommends that Indonesia increase cooperation with Korea in fisheries technology through the Marine Technology Cooperation Research Center (MTCRC). This cooperation will help Indonesia improve its fishing technology and fisheries resource management system.
Keywords: Fishing Technology; Korea; Indonesia; Efficiency; Quality and Sustainability